Effect of cationic surfactant on the physicochemical and antibacterial properties of colloidal systems (emulsions and microemulsions) - M. K. D. Rambo; R. F. Lins; F. L. N Silva; A. Alonso; M. C. D. Rambo; J. E. C Leal; D. de Sousa-Neto (Brazilian Journal of Biology, 2024)
Abstract Colloidal systems have been used to encapsulate, protect and release essential oils in mouthwashes. In this study, we investigated the effect of cetylpyridinium chloride (CPC) on the physicochemical properties and antimicrobial activity of oil-in-water colloidal systems containing tea tree oil (TTO) and the nonionic surfactant polysorbate 80. Our main aim was to evaluate whether CPC could improve the antimicrobial activity of TTO, since this activity is impaired when this essential oil is encapsulated with polysorbate 80. These systems were prepared with different amounts of TTO (0-0.5% w/w) and CPC (0-0.5% w/w), at a final concentration of 2% (w/w) polysorbate 80. Dynamic light scattering (DLS) results revealed the formation of oil-swollen micelles and oil droplets as a function of TTO concentration. Increases in CPC concentrations led to a reduction of around 88% in the mean diameter of oil-swollen micelles. Although this variation was of only 20% for the oil droplets, the samples appearance changed from turbid to transparent. The surface charge of colloidal structures was also markedly affected by the CPC as demonstrated by the transition in zeta potential from slightly negative to highly positive values. Electron paramagnetic resonance (EPR) studies showed that this transition is followed by significant increases in the fluidity of surfactant monolayer of both colloidal structures. The antimicrobial activity of colloidal systems was tested against a Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureaus) bacteria. Our results revealed that the inhibition of bacterial growth is observed for the same CPC concentration (0.05% w/w for E. coli and 0.3% w/w for S. aureus) regardless of TTO content. These findings suggest that TTO may not act as an active ingredient in polysorbate 80 containing mouthwashes.